The diagnostic accuracy of contrast echocardiography in patients with suspected cardiac masses: A preliminary multicenter, cross-sectional study - Li, Ying; Ren, Weidong; Wang, Xin; Xiao, Yangjie; Feng, Yueqin; Shi, Pengli; Sun, Lijuan; Wang, Xiao; Yang, Huan; Song, Guang (Frontiers in Cardiovascular Medicine, 2022)
Background To evaluate the diagnostic accuracy of contrast echocardiography (CE) in patients with suspected cardiac masses. Methods A multicenter, prospective study involving 108 consecutive patients with suspected cardiac masses based on transthoracic echocardiography performed between November 2019 and December 2020 was carried out. CE examinations were performed in all patients. The echocardiographic diagnosis was established according to the qualitative (echogenicity, boundary, morphology of the base, mass perfusion, pericardial effusion, and motility) and quantitative (area of the masses and peak intensity ratio of the masses and adjacent myocardium A1/A2) evaluations. Results Final confirmed diagnoses were as follows: no cardiac mass (n = 3), pseudomass (n = 3), thrombus (n = 36), benign tumor (n = 30), and malignant tumor (n = 36). ROC analysis revealed the optimal A1/A2 with cutoff value of 0.295 for a cardiac tumor from a thrombus, with AUC, sensitivity, specificity, PPV, and NPV of 0.958 (95% confidence interval (CI): 0.899–0.988), 100, 91.7, 95.7, and 100%, respectively. CE was able to distinguish malignant from benign tumors with an AUC of 0.953 (95% CI: 0.870–0.990). Multivariate logistic regression analysis revealed that tumor area, base, and A1/A2 were associated with the risk of malignant tumor (OR = 1.003, 95% CI: 1.00003–1.005; OR = 22.64, 95% CI: 1.30–395.21; OR = 165.39, 95% CI: 4.68–5,850.94, respectively). When using A1/A2 > 1.28 as the only diagnostic criterion to identify the malignant tumor, AUC, sensitivity, specificity, PPV, and NPV were 0.886 (95% CI: 0.784–0.951), 80.6, 96.7, 96.7, and 80.7%, respectively. Conclusion CE has the potential to accurately differentiate cardiac masses by combining qualitative and quantitative analyses. However, more studies with a large sample size should be conducted to further confirm these findings. Clinical trial registration http://www.chictr.org.cn/, identifier: ChiCTR1900026809.